PENGARUH MEDIA PANCING TERHADAP KEMAMPUAN BERHITUNG 1 – 10 ANAK KELOMPOK A USIA 4 – 5 TAHUN DI TK INFARUL GHOY I DESA TRITUNGGAL KECAMATAN BABAT KABUPATEN LAMONGAN - Ismaul Yasiro; Aisyah (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This research was motivated by the problem of the low counting ability of 1-10 children in Infarul Ghoy I Kindergarten because many children still do not understand the numbers 1-10, such as saying number symbols, conceptualizing numbers, stating the order of numbers, arranging numbers. Therefore, researchers will conduct research using fishing media as a medium that can facilitate counting learning activities. This research aims to find out whether fishing media can influence the ability to count 1-10 in group A children of Infarul Ghoy I Kindergarten, Tritunggal Village, Babat District, Lamongan Regency. This research is a one-group pretest posttest design research. Data analysis applied in this research was pretest and posttest techniques (t test). The subjects of this research were 25 children aged 4 - 5 years, consisting of 17 male students and 8 female students. make learning activities easier to count. The results of the research show that the calculated t test results have a Sig. (2-tailed) of 0.000 < 0.05. So the Null Hypothesis is rejected. Thus it can be stated that